Enhanced Mechanical Properties of Organo-Clay Based UHMWPE Nanocomposite Films - R. Ahmed; K. Ali Syed (Journal of Basic & Applied Sciences, 2016)
The proposed study investigated the effect of organo-clay contents in ultra-high molecular weight polyethylene (UHMWPE) gel/solution cast films. The organo-clay was loaded in the range of 1 to 5 % (wt. / wt.), based on polymer content, to prepare UHMWPE nanocomposite films. The UHMWPE nanocomposite films were drawn up to 15 times below their melting point. Un-drawn and drawn UHMWPE nanocomposite films were subjected to mechanical and optical characterizations. The enhanced modulus (> 170 % higher than un-drawn films for 5 % organo-clay loadings at draw ratio of 15) and higher force at break (about 150 % higher than un-drawn films) without the loss of inherent optical transparency, even at higher organo-clay loadings, are reported. The findings in this study will broaden the engineering applications of UHMWPE nanocomposite films.